The Impact of Online Ordering on Food and Beverage Sales at Pokke Sushi - Vienna Artina Sembiring; Wisnu Prasetyo (Journal Hotspot, 2021)
This study aims to determine the results of how much online ordering of food and beverages on sales at Pokke Sushi. This research method uses decriptive correlational method. The population in this study were consumers or buyers at Pokke Sushi from various groups ranging from students, university students, entrepreneurs and others. The technieque of collecting data is by distributing accidental questionnaires, observing and reading books or journals related to the tittle. The results of this study are (1) Online food ordering applications can affect sales at Pokke Sushi by 58% (2) the average respondent is satisfied with what Pokke Sushi provides, with a correlation value of 0.851 which means there is a very strong relationship. Against online ordering and sales at Pokke Sushi